Indonesia’s New Model of Bilateral Investment Treaty: Comparison with Brazil - Putri, Resha Roshana (Padjadjaran Journal of International Law, 2019)
AbstractIn the past few years, there has been a surge in lawsuits against the mechanism for resolving international investment disputes through the Investors State Dispute Settlement (ISDS) forum proposed by foreign investors who are host states, including Indonesia. Most of the claims are due to policies of the host country which are intended to protect the basic rights of the people such as the right to health, the right to a healthy environment, taxes, as well as the minimum standard of wages for workers. This policy provides a loss for foreign investors and is considered as a violation of the Bilateral Investment Treaty (BIT). BIT is often recognized to be detrimental to Indonesia, because it potentially can disrupt the sovereignty of the country, especially when it is dealing with foreign investors disputes. By using a comparative juridical approach as a research method, this article tries to provide sufficient rules for new BIT model by comparing with Brazil. Brazil?s Cooperation and Investment Facilitation Agreement (CIFA) has succeeded in reforming Brazil investment regime (specifically on its BITs). Indonesia therefore needs to change several provisions in its BITs as also provided in CIFA Brazil, which is not member of the ICSID Convention.Keywords: BIT, CIFA, Investor State Dispute Settlement, ICSID AbstrakBeberapa tahun terakhir, ada lonjakan tuntutan hukum terhadap mekanisme penyelesaian sengketa investasi internasional melalui Investor State Dispute Settlement (ISDS), sebuah forum yang diusulkan oleh investor asing yang menjadi negara tuan rumah termasuk Indonesia. Sebagian besar tuntutan disebabkan oleh kebijakan negara tuan rumah yang bertujuan untuk melindungi hak-hak dasar masyarakatnya seperti hak atas kesehatan, hak atas lingkungan yang sehat, pajak, juga standar minimum upah pekerja. Kebijakan ini berdampak pada kerugian bagi investor asing dan dianggap sebagai pelanggaran Bilateral Investment Treaty (BIT). BIT seringkali dianggap merugikan bagi Indonesia, karena dapat mengganggu kedaulatan negara, khususnya ketika berhadapan dengan sengketa internasional dengan investor asing. Dengan menggunakan pendekatan yuridis normatif dan metode perbandingan, artikel ini mencoba untuk memberikan aturan hukum yang memadai untuk model BIT yang baru dengan melakukan perbandingan dengan BIT Brazilia yang disebut Cooperation and Investment Facilitation Agreement (CIFA). Brazil dipilih karena merupakan negara yang berhasil melakukan reformasi terhadap rezim investasinya, khususnya pada BIT. Hasil dari perbandingan tersebut adalah Indonesia perlu merubah beberapa ketentuan dalam BITs nya, seperti yang terkadung dalam CIFA di Brazil, yang bukan merupakan negara anggota dari Konvensi ICSID.Kata Kunci: BIT, CIFA, Penyelesaian Sengketa Investor-Negara, ICSID